1997
DOI: 10.1080/08869634.1997.11746013
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives On the Role of the Lateral Pterygoid Muscle and the Sphenomandibular Ligament in Temporomandibular Joint Function

Abstract: The lateral pterygoid muscle plays an important role in the movement of the mandible and has been studied from several points of view, including structural and functional anatomy. What matters clinically is the relative position of the muscle fibers attached medially to the mandibular condyle. In the following study, we observed not only the attachment of the lateral pterygoid muscle fibers to the articular disk, but also the relative position of the mandibular condyle to a base line set up on the mandibular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…In relation to the spheno-mandibular ligament, there is agree with the findings of Abe et al, 171 who found that this ligament was inferiorly fixed to the mandible and superiorly fixed to the sphenoid spine and the anterior malleolar ligament as shown by personal dissections on human temporal bone specimens ( Figure 15). Both may be tensed in a marked overclosure position, also stretching oscicular balance.…”
Section: First Bone Common Passages Explorationsupporting
confidence: 81%
“…In relation to the spheno-mandibular ligament, there is agree with the findings of Abe et al, 171 who found that this ligament was inferiorly fixed to the mandible and superiorly fixed to the sphenoid spine and the anterior malleolar ligament as shown by personal dissections on human temporal bone specimens ( Figure 15). Both may be tensed in a marked overclosure position, also stretching oscicular balance.…”
Section: First Bone Common Passages Explorationsupporting
confidence: 81%
“…The tendons may accommodate a great number of muscular fibers insertions on a little surface (Chong and Evans, 1982), and supply the mechanical strength for muscle activity (Sato et al, 1992;Abe et al, 1997;Aimonetti et al, 2005). Thus, it is suggested that the medial anterior layer, which inserts on the edge of the angular process, through a strong tendon, supplies mechanical strength for masticatory activity.…”
Section: Discussionmentioning
confidence: 97%
“…Then the AML runs from the petrotympanic fissure to the Sphenomandibular ligament (SML) (Burch, 1970;Toledo-Filho et al, 1985;Komori et al, 1986;Sencimen et al, 2008). The attachments of the SML, AML and DML to the malleus are differ (Toledo-Filho et al, 1984; Rodríguez-Vázquez et al, 1998; Abe et al, 1997;Ramírez, 2007). However, the detailed structure of the TML between the petrotympanic fissure and the tympanic cavity is unknown.…”
Section: Introductionmentioning
confidence: 99%